Double principal coordinate analysis(DPCoA) for fishes in Lake Mihaba with respect to their diet composition. - Balbon, Shiena Mae P. (2010)
Lake Mihaba, one of the fishing camp in Agusan Marsh, is a home of a variety of fish species. In this camp, there have been several studies on the species composition which include Talde et. al. (2004), who used dietary index to measure the important food items that the fishes consumed. However, they did not consider differences between fish species with respect to their differences in food items. Using the same data gathered by Talde et al. (2004), this study made use of DPCoA to analyze the fish diet composition in Lake Mihaba of Agusan Marsh. Abundance and incidence distributions were considered in this study. The abundance distribution comprises the volume of food items consumed by fish species while the incidence distribution consists of the occurrence of food items in the guts of fish species. Further, two dissimilarity measures were developed. Using the first dissimilarity matrix was able to show fish species with the same taxonomic features shared the same food items. Nonetheless, fish species which does not belong to the group were also found out to compete with the same food items. On the other hand, the second dissimilarity matrix was able to show which fish species were competing for the identified food items regardless of their taxonomic feature.